The Impact of COVID-19 on Access to Mental Healthcare Services - Benjamin Harrell; Luca Fumarco; Patrick Button; David J. Schwegman; Kyla Denwood (Institute of Labor Economics (IZA), 2023)
The COVID-19 pandemic increased the rate of mental health disorders, as well as demand for mental health services. It remains unclear, however, the extent to which the pandemic impacted access to mental health services. Using data from an audit field experiment, we examine the impact of COVID-19 on access to mental health care appointments in the United States. This experiment ran from January to May 2020 and overlapped with the initial onset of the COVID-19 pandemic. We find that increased intensity of COVID-19—measured by daily cases, daily fatalities, and weekly excess deaths—is associated with decreased access to mental health care appointments.
Keywords: C93; I14; J16; I11; I18; J15; 330; mental health care; audit; COVID-19